Painful vision loss during air travel after vitrectomy with air tamponade: a case report - Jessica Emrich; Peter Charbel Issa; Carmen Baumann (Journal of Medical Case Reports)
Abstract Background While the potentially hazardous effects of intraocular perfluorocarbon gases during air travel have been recognized, the equivalent risk of intraocular air tamponade is less known and has, to the best of our knowledge, not been reported yet. Case presentation A 52-year-old white female experienced a complete loss of vision and pain in her left eye during air travel following pars plana vitrectomy with air tamponade. Clinical and multimodal imaging findings only a few hours after emergency landing indicated a transient central retinal artery occlusion due to a significant increase in intraocular pressure during the flight. Conclusion Air travel, even with a relatively small volume of residual air tamponade, can lead to potentially serious complications.